PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN FIQIH MADRASAH TSANAWIYAH PONDOK PESANTREN AN-NUR TANGKIT MUARO JAMBI - Ahmad Ridwan; Madyan Madyan; Bastian Feri; Ronia Azizah (Lafadz Jaya Publisher, 2023)
This research is collaborative class action research (PTK) which is analyzed descriptively qualitatively. In collecting data used the method of observation, tests, interviews and documentation. The observation method is used to measure teacher and student activity per cycle. The test method is used to determine students' learning abilities after participating in learning using the Problem Based Learning learning model. The interview method was used to find out opinions and descriptions at Madrasah Tsanawiyah Pondok Pesantren An-Nur Tangkit Muaro Jambi. And the documentation method is used to describe what happened in class during the learning process. The results of this study indicate that the use of the Problem Based Learning learning model is able to improve the learning outcomes of students in class VIII C of Madrasah Tsanawiyah Pondok Pesantren An-Nur Tangkit Muaro Jambi, namely 52% in cycle I, 76% in cycle II and 84% in cycle III. Based on the results of the analysis of the data obtained, it can be concluded that learning Fiqh using the Problem Based Learning learning model can improve student learning outcomes on the subject matter of zakat from increasing post-test scores in each cycle.